Correction: Effect of hydrophobically modified PEO polymers (PEO-dodecyl) on oil/water microemulsion properties: in vitro and in silico investigations. Issue 18 (11th March 2021) - Khatouri, M.; Ahfir, R.; Lemaalem, M.; El Khaoui, S.; Derouiche, A.; Filali, M.
Abstract : Correction for 'Effect of hydrophobically modified PEO polymers (PEO-dodecyl) on oil/water microemulsion properties: in vitro and in silico investigations' by M. Khatouri et al., RSC Adv., 2021, 11, 7059–7069, DOI: ; 10.1039/D0RA09804C .